Application of Problem Based Learning Model in Improving Students' Critical Thinking Skills in Science Subjects in Class V SD Negeri 72 Kendari - sitti hatijah (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to improve students' critical thinking skills in science subjects in class V SD Negeri 72 Kendari. The type of research is Classroom Action Research (CAR). A distinctive characteristic of classroom action research is the existence of specific actions to improve the teaching and learning process in the classroom. Based on data analysis and discussion, the critical thinking skills of fifth-grade students at SD Negeri 72 Kendari in science subjects can be improved by applying the Problem Based Learning learning model. This can be seen from the test results in the first cycle, with a completeness percentage of 46.47% with an average value of 72.22. The completeness of student learning outcomes has increased in the second cycle to 83.33%, with an average value of 84.00. These results indicate that the implementation of the action was successfully implemented because the predetermined performance indicators have been achieved.